2020
DOI: 10.1101/2020.01.07.897579
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SparkINFERNO: A scalable high-throughput pipeline for inferring molecular mechanisms of non-coding genetic variants

Abstract: AbstractSummaryWe report SparkINFERNO (Spark-based INFERence of the molecular mechanisms of NOn-coding genetic variants), a scalable bioinformatics pipeline characterizing noncoding GWAS association findings. SparkINFERNO prioritizes causal variants underlying GWAS association signals and reports relevant regulatory elements, tissue contexts, and plausible target genes they affect. To achieve this, the SparkINFERNO algorithm integrates GWAS su… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…FILER provides query/search functions ( Section 3.3 ), allowing to easily integrate and query datasets using custom genetic and genomic analysis workflows such as INFERNO (Amlie-Wolf et al ., 2018; Kuksa et al ., 2020) (see Section 3.4 for an example). The scalable interface of FILER allows analysis and annotation of user-generated experimental data (e.g., for a particular biological condition) with reference FILER datasets across various tissues/cell types and data sources ( Section 3.3 ), facilitating research studies across different human diseases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…FILER provides query/search functions ( Section 3.3 ), allowing to easily integrate and query datasets using custom genetic and genomic analysis workflows such as INFERNO (Amlie-Wolf et al ., 2018; Kuksa et al ., 2020) (see Section 3.4 for an example). The scalable interface of FILER allows analysis and annotation of user-generated experimental data (e.g., for a particular biological condition) with reference FILER datasets across various tissues/cell types and data sources ( Section 3.3 ), facilitating research studies across different human diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Example of integrating FILER (middle part of the figure) with a custom aggregation and analysis workflow (bottom of the figure), SparkINFERNO (Kuksa et al ., 2020) for high-throughput non-coding variant analysis (inputs at the top).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both Ensembl ID (Yates et al, 2020) and HGNC (Braschi et al, 2019) gene symbols are reported for each genetic variant. For each ADVP variant, the co-localized genomic element (e.g., promoter, intron, UTR, repeat, intergenic) is reported based on the genomic partition information (Amlie-Wolf et al, 2018; Kuksa et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…For each genetic variant co-localized with one or more genes, both EnsemblID [27] and HGNC [28] symbols for the gene(s) are reported. For each ADVP variant, the co-localized genomic element is reported based on the genomic partition information [29, 30].…”
Section: Methodsmentioning
confidence: 99%